Short communication: Diversity of bird species in Air Telang Protected Forest, South Sumatra, Indonesia - SYAIFUL EDDY; DIAN MUTIARA; ROSWITHA YEMIMA TIUR MEDISWATI; RAMA GIVATI RAHMAN; NORIL MILANTARA; MOHAMMAD BASYUNI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Eddy S, Mutiara D, Mediswati RYT, Rahman RG, Milantara N, Basyuni M. 2021. Short communication: Diversity of bird species in Air Telang Protected Forest, South Sumatra, Indonesia. Biodiversitas 22: 5274-5279. Birds belong to the mangrove forest ecosystem, which is important biodiversity for life and must be maintained. This study aimed to examine the diversity of bird species in Air Telang Protected Forest (ATPF) which has experienced massive degradation. Birds' observation was carried out using the purposive sampling method by exploring predetermined areas with binoculars and cameras and direct observation. Birds were identified by analyzing their morphology, sound, and color. The research data obtained a total of 38 bird species that consist of 13 orders and 22 families. In addition, the results of this study obtained nine species of migratory birds and two species with near threatened (NT) status based on the IUCN Red List Category. This study is the first bird species inventory and identification research conducted in ATPF.